The Security System of the United Nations (A Theoretical Approach) - Chajkowska, Katarzyna (Acta Agraria Debreceniensis, 2012)
In contemporary world, influenced by globalization, security is one of the most discussed issues. It is almost commonly accepted that security should be regulated within some kind of international system. What should be agreed on are the nature of subjects within the system, the kind of resources, ways to control it and finally, how to achieve an agreement within the system’s framework. Thus the objective of this article is to show the axiological premises that underlie normative regulations on the above issues. Significant diversion in this sphere is observed within the Organization of United Nations. The following article analyses the UN documents, with a particular emphasis on the Millennium documents, determining the long-term perspective of actions. The article shall also try to define the issues not covered in the UN regulations and determine what dilemmas UN unsuccessfully tries to tackle.